Implementação de modelos de redes de Petri em hardware de lógica reconfigurável - Antiqueira, Perci Ayres (2011)
In this research work, was performed a study of main types of hardware modeling tools searching to verify the advantages of utilizing for modeling dynamic and concurrent systems and for its hardware implementation. It was observed that even though there are tools for this purpose, exists some points that may be worked out to facilitate access to this technology. So, was developed a method for facilitate implementation of systems modeled in Petri nets, in reconfigurable logic hardware. For that, was utilized a capture software where, from the graphic of the Petri net model, is generated a description in PNML (Petri Net Markup Language) format. From this description, is generated a hardware description file in VHDL (VHSIC Hardware Description Language) format, that may be loaded in a reconfigurable logic circuit. To make possible this stage, was performed the development of tool that generate a file in VHDL language from the description in PNML format. The developed tool is described in details, showing all stages and criteria utilized in the conversion. To validate the method, is showed an application example for this toll with the implementation in FPGA (Field Programmable Gate Arrow), of a Petri net modeling a hypothetic industrial plant. Finally, a performance comparison is made between the model executed in hardware and the model executed in software.